2016
DOI: 10.4209/aaqr.2015.08.0496
|View full text |Cite
|
Sign up to set email alerts
|

Local and Regional Contributions to Fine Particle Pollution in Winter of the Yangtze River Delta, China

Abstract: The Yangtze River Delta (YRD) is one of the most developed and heavily polluted regions in China. Understanding the origin of fine particles is necessary for policy making on air pollution control in this region. However, the current studies on quantifying the contributions from different emission source regions are limited, especially for winter pollution. In this study, field observations and scenario analysis simulations were performed by using the Weather Research and Forecasting and Community Multi-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…Thirdly, the wind speed is slightly overestimated over the region, with NMB and NME values of 28 % and 33 %, respectively, causing fast dispersion of air pollutants. Overall, these statistics for both the meteorological parameters and simulated PM 2.5 are generally consistent with the results in other published modeling studies (Zheng et al, 2015;Wang et al, 2014;Zhang et al, 2011;Fu et al, 2016;Li et al, 2015a, b), which suggests that the simulation performance is acceptable.…”
Section: Model Performancesupporting
confidence: 90%
“…Thirdly, the wind speed is slightly overestimated over the region, with NMB and NME values of 28 % and 33 %, respectively, causing fast dispersion of air pollutants. Overall, these statistics for both the meteorological parameters and simulated PM 2.5 are generally consistent with the results in other published modeling studies (Zheng et al, 2015;Wang et al, 2014;Zhang et al, 2011;Fu et al, 2016;Li et al, 2015a, b), which suggests that the simulation performance is acceptable.…”
Section: Model Performancesupporting
confidence: 90%
“…In general, model predicted data are lower than the observed data with the NMB value of -22% to -30%, the NME value of 45% to 47% and the I value of 0.67 to 0.70 (Table 2). Overall, these statistics for both the meteorological parameters and simulated PM2.5 are generally consistent with the results in other published modelling studies (Zheng et al, 2015;Wang et al, 2014;Zhang et al, 2011;Fu et al, 2016;Li et al, 2015b;Li et al, 2015a), which suggests that the simulation performance is acceptable.…”
Section: Model Performancesupporting
confidence: 90%
“…Furthermore, some studies had attempted to identify the correlation between pollutants and meteorological factors [24,25]. The results have shown that the low planetary boundary layer height (PBLH) [26], the weakening of northerly winds [27], the decrease of relative humidity [28], and the increase of sea level temperature [29] have also led to the increase of winter haze in eastern China.…”
Section: Wrf-chem Model Configurationmentioning
confidence: 99%